Fusobacterium nucleatum Promotes the Development of Ulcerative Colitis by Inducing the Autophagic Cell Death of Intestinal Epithelial - Su, Wenhao; Chen, Yongyu; Cao, Pan; Chen, Yan; Guo, Yuanmei; Wang, Siwei; Dong, Weiguo (Frontiers in Cellular and Infection Microbiology, 2020)
There is a growing body of evidence which suggests that intestinal microbiota, especially Fusobacterium nucleatum (F. nucleatum), are associated with intestinal immune disease such as ulcerative colitis (UC). The mechanism by which F. nucleatum promotes intestinal epithelial cell (IEC) death remained undefined. Here, we investigated the potential mechanisms about how F. nucleatum aggravates IEC death in UC. We first detected the abundance of F. nucleatum in UC tissues and analyzed its relationship with the clinical characteristics of UC. Next, we explored whether F. nucleatum promotes intestinal epithelial cell death in vitro and in vivo. Furthermore, we extracted lipopolysaccharide (LPS) of the F. nucleatum and examined whether F. nucleatum exacerbates UC via LPS. Our results indicated that F. nucleatum was abundant in UC tissues and was correlated with clinical characteristics. In addition, we demonstrated that F. nucleatum and its LPS aggravated IEC death by promoted IEC autophagy. Furthermore, autophagy inhibitors, chloroquine (CQ), 3-methyladenine (3-MA) or Atg5 silencing prevented IEC death mediated by F. nucleatum, which suggests F. nucleatum may contribute to UC by activating autophagic cell death. All our results uncover a vital role of F. nucleatum in autophagic cell death and UC, giving rise to a new sight for UC therapy by inhibiting excessive IEC autophagy and autophagic cell death.